2011
DOI: 10.3109/03009734.2011.624649
|View full text |Cite
|
Sign up to set email alerts
|

The type I interferon system in the etiopathogenesis of autoimmune diseases

Abstract: Many patients with systemic autoimmune diseases have signs of a continuous production of type I interferon (IFN) and display an increased expression of IFN-α-regulated genes. The reason for the on-going IFN-α synthesis in these patients seems to be an activation of plasmacytoid dendritic cells (pDCs) by immune complexes (ICs), consisting of autoantibodies in combination with DNA or RNA-containing autoantigens. Such interferogenic ICs are internalized via the FcγRIIa expressed on pDCs, reach the endosome, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
84
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 99 publications
(107 reference statements)
1
84
0
7
Order By: Relevance
“…These cells, known as plasmacytoid DCs (pDCs), are the most potent producers of type I IFNs, a functional characteristic attributed to constitutive expression of TLR7, TLR9, and IRF7 and likely signaling from a unique intracellular compartment (24)(25)(26)(27). The involvement of pDCs in lupus is further suggested by the reduced frequency of these cells in patient blood together with increases in afflicted organs, presumably caused by the attraction of activated pDCs to inflammatory sites (10). Similar increases have been noted in inflammatory tissues of patients with Sjögren's syndrome (28), rheumatoid arthritis (29,30), dermatomyositis (31), and psoriasis (32).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These cells, known as plasmacytoid DCs (pDCs), are the most potent producers of type I IFNs, a functional characteristic attributed to constitutive expression of TLR7, TLR9, and IRF7 and likely signaling from a unique intracellular compartment (24)(25)(26)(27). The involvement of pDCs in lupus is further suggested by the reduced frequency of these cells in patient blood together with increases in afflicted organs, presumably caused by the attraction of activated pDCs to inflammatory sites (10). Similar increases have been noted in inflammatory tissues of patients with Sjögren's syndrome (28), rheumatoid arthritis (29,30), dermatomyositis (31), and psoriasis (32).…”
mentioning
confidence: 99%
“…These results were integrated in a more comprehensive scheme following the demonstration that type I IFN induction by these complexes is mediated by the engagement of endosomal Toll-like receptors (TLRs) (9)(10)(11). Similarly, antigenic cargo containing nucleic acids was found to promote B-cell proliferation in a TLR9-or TLR7-dependent manner, with this effect enhanced by type I IFN signaling (9,12,13).…”
mentioning
confidence: 99%
“…However, recent studies have demonstrated that IFN-I signaling could play deleterious roles in some normal biological functions, especially when cells undergo excessive activated IFN-I signaling. It has been reported that uncontrolled activated IFN-I signaling contributes to autoimmune diseases, such as systemic lupus erythematosus, rheumatoid arthritis, and Aicardi-Goutières syndrome (6,7). IFN-I also has important effects on lethality in diverse models of sepsis or endotoxic shock (8).…”
mentioning
confidence: 99%
“…This family consists of different a genes (Ifna), 13 in humans and 14 in mice, and one b IFN gene (Ifnb), both of which signal through the heterodimeric receptor complex, consisting of IFNAR1 and IFNAR2. Type I IFNs have been associated with autoimmune diseases because type I IFN-inducible genes are upregulated in some autoimmune diseases, displaying a so-called IFN signature (13)(14)(15). This is an upregulation of type I IFN-inducible genes or genes containing IFN-sensitive response elements (ISREs) found in tissues such as skin lesions in psoriasis and the inflamed joints of rheumatoid arthritis patients (16)(17)(18)(19).…”
mentioning
confidence: 99%